2007
DOI: 10.1128/jb.01707-06
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sinorhizobium meliloti Triose Phosphate Isomerase Genes

Abstract: A Tn5 mutant strain of Sinorhizobium meliloti with an insertion in tpiA (systematic identifier SMc01023), a putative triose phosphate isomerase (TPI)-encoding gene, was isolated. The tpiA mutant grew more slowly than the wild type on rhamnose and did not grow with glycerol as a sole carbon source. The genome of S. meliloti wild-type Rm1021 contains a second predicted TPI-encoding gene, tpiB (SMc01614). We have constructed mutations and confirmed that both genes encode functional TPI enzymes. tpiA appears to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 55 publications
0
28
0
Order By: Relevance
“…Glyceraldehyde 3-phosphate is subsequently isomerized by triose phosphate isomerase to dihydroxyacetone phosphate, and a hexose is synthesized via an aldolase reaction, yielding fructose 1,6-bisphosphate. It has recently been shown that S. meliloti contains two triose phosphate isomerases (48). It has been shown that tpiA plays a role in central metabolic metabolism (48), whereas tpiB appears to be necessary for erythritol catabolism in S. meliloti and Rhizobium leguminosarum (48,61).…”
Section: Resultsmentioning
confidence: 99%
“…Glyceraldehyde 3-phosphate is subsequently isomerized by triose phosphate isomerase to dihydroxyacetone phosphate, and a hexose is synthesized via an aldolase reaction, yielding fructose 1,6-bisphosphate. It has recently been shown that S. meliloti contains two triose phosphate isomerases (48). It has been shown that tpiA plays a role in central metabolic metabolism (48), whereas tpiB appears to be necessary for erythritol catabolism in S. meliloti and Rhizobium leguminosarum (48,61).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, CymMV infection also dramatically induces TRXh expression in P. amabilis leaves, in consistence with the previous result. PGK is involved in glycolysis and tricarboxylic acid (TCA) cycle and plays important roles in energy production [21]. PGK expression was significantly decreased only in CymMV-infected P. amabilis leaves, indicating that the energy metabolism of the plant host was damaged severely after CymMV infection.…”
Section: Proteins Specifically Regulated By the Infection With Cymmvmentioning
confidence: 99%
“…Similarly, our results showed that ORSV infection enhanced Rubisco expression in leaves, implying that the modified Rubisco struc-ture is associated with different viral pathogens. TPI is involved in glycolysis and TCA cycle and plays important roles in energy production [21]. IDH is a ratelimiting enzyme in TCA cycle and plays important roles in energy metabolism, amino acid synthesis and vitamin synthesis [23,24].…”
Section: Proteins Specifically Regulated By Orsv Infectionmentioning
confidence: 99%
“…The in-frame deletion mutations of sma0113 and sma0114 were complemented by inserting wild-type copies of the genes into the rhamnose-binding protein gene (smc02324) using pCAP87. pCAP87 is a suicide plasmid containing a constitutive trp promoter upstream of the multiple cloning site and an internal fragment of smc02324 which targets the plasmid to an operon that encodes a rhamnose transport system (1,35,45). Wild-type copies of sma0113 and sma0114 were cloned into plasmid pCAP87.…”
Section: Methodsmentioning
confidence: 99%